TINJAUAN HUKUM PERDATA TENTANG PENGGUNAAN KONTRAK TAK TERTULIS DALAM KEGIATAN PERDAGANGAN - Anisah Daeng Tarring; Andi Sri Rezky Wulandari (Jurnal Hukum Ius Publicum, 2024)
This study examines the use of unwritten contracts in trade activities, with the aim of understanding the applicable practices and their implications for civil law in Indonesia. The research method used is qualitative with an approach to document study and in-depth interviews with business actors and legal practitioners. The results of the study show that unwritten contracts are often chosen because of the speed and flexibility factors in day-to-day business transactions, although this carries significant legal risks, including ambiguity in the enforcement of the rights and obligations of the parties. The study also explores how civil law provisions can be interpreted and applied in cases where unwritten contracts are the source of disputes. This study provides recommendations to increase legal awareness among business actors and proposes policy changes that can strengthen the legal framework for the use of written contracts in trade. The implications of this research are relevant for the development of more transparent and accountable trade laws and practices.